Recent results from the Penning trap mass spectrometer ISOLTRAP - Blaum, Klaus; Kluge, Heinz-Jürgen (Nuclear physics. B, Particle physics, 2004)
In the last few years a number of new scientific highlights have been obtained by ISOLTRAP, the tandem Penning trap mass spectrometer for on-line mass measurements of short-lived radionuclides. The precise determination of nuclear binding energies far from stability includes nuclei that are produced at rates of 100 ions/s and with half-lives below 100 ms. The mass resolving power reaches 107 and the uncertainty of the resulting mass values has been pushed down to 1⋅10−8. In this article recent ISOLTRAP mass measurements are summarized and the current status of ISOLTRAP is presented.
Gesehen am 04.03.2020